2023
DOI: 10.14256/jce.3343.2021
|View full text |Cite
|
Sign up to set email alerts
|

A site survey of damaged RC buildings in İzmir after the Aegean sea earthquake on October 30, 2020

Abstract: An earthquake with a magnitude of Mw = 6.6 and a depth of approximately 16.5 km occurred on 30 October 2020 off the cost of Samos, a Greek island 35 km southwest of Seferihisar, a town in İzmir. The earthquake caused several collapses and severe structural damage in approximately 6,000 buildings, specifically in the Bayraklı District in İzmir Bay. This paper presents the observations and findings of a technical team that visited the earthquake-affected areas immediately after an earthquake. Eleven partially or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…The basic issues related to the extensive damage and collapse of RC buildings in the Kahramanmaraş earthquakes are explained in this section as shown in Figure 20. It should be noted that the issues listed above are common problems encountered during earthquake site investigations here, and elsewhere, in Türkiye [1,44,45]. The damage and failure of many RC buildings can be explained using these basic problems, among others.…”
Section: Issues Related To Building Damagementioning
confidence: 93%
See 2 more Smart Citations
“…The basic issues related to the extensive damage and collapse of RC buildings in the Kahramanmaraş earthquakes are explained in this section as shown in Figure 20. It should be noted that the issues listed above are common problems encountered during earthquake site investigations here, and elsewhere, in Türkiye [1,44,45]. The damage and failure of many RC buildings can be explained using these basic problems, among others.…”
Section: Issues Related To Building Damagementioning
confidence: 93%
“…Payments were also made to the pool and the inspecting company was paid from this pool. Therefore, it can be concluded that the inspection services of construction work in Türkiye became more reliable after 2019 [1,45].…”
Section: Issues Related To Building Inspectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earthquakes cause huge property damage and deprive many people of their lives, and approximately two earthquakes occur per minute on the earth [1]. The conventional seismic isolation methods include passive control, active control, and hybrid control techniques [2][3][4][5][6], and generally, these techniques often have little effect on large earthquakes [7]. A periodic structure made of phononic crystals and locally resonant metamaterials acts as seismic wave barriers to greatly attenuate the amplitude of seismic waves before they reach the protected target [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%